Pelaksanaan Pencabutan Hak Pembebasan Bersyarat bagi Klien Pemasyarakatan yang Melakukan Tindak Pidana pada Masa Tenggang (Studi Kasus di Balai Pemasyarakatan Kelas I Surabaya) - Julianne, Riesa Crysanti; Indawati, Yana (Universitas Gorontalo, 2025)
This research aims to analyze the implementation of the revocation of parole rights for correctional clients who commit criminal acts during the grace period, with a case study at the Surabaya Class I Correctional Center. Using an empirical juridical approach involving field surveys and document analysis, this study found that the revocation of parole rights is often caused by violations of the conditions set out in the laws and regulations. Barriers to the implementation of this revocation include a lack of coordination and consistent application of the law. This study concludes that the parole revocation process requires improvements in coordination between relevant parties as well as stricter law enforcement to ensure the effectiveness of the parole system.